NKp30 isoforms and NKp30 ligands are predictive biomarkers of response to imatinib mesylate in metastatic GIST patients. (2nd January 2017) - Rusakiewicz, Sylvie; Perier, Aurélie; Semeraro, Michaela; Pitt, Jonathan M.; Pogge von Strandmann, Elke; Reiners, Katrin S.; Aspeslagh, Sandrine; Pipéroglou, Christelle; Vély, Frédéric; Ivagnes, Alexandre; Jegou, Sarah; Halama, Niels; et al.
ABSTRACT: Despite effective targeted therapy acting on KIT and PDGFRA tyrosine kinases, gastrointestinal stromal tumors (GIST) escape treatment by acquiring mutations conveying resistance to imatinib mesylate (IM). Following the identification of NKp30-based immunosurveillance of GIST and the off-target effects of IM on NK cell functions, we investigated the predictive value of NKp30 isoforms and NKp30 soluble ligands in blood for the clinical response to IM. The relative expression and the proportions of NKp30 isoforms markedly impacted both event-free and overall survival, in two independent cohorts of metastatic GIST. Phenotypes based on disbalanced NKp30B/NKp30C ratio (ΔBC low ) and low expression levels of NKp30A were identified in one third of patients with dismal prognosis across molecular subtypes. This ΔBC low blood phenotype was associated with a pro-inflammatory and immunosuppressive tumor microenvironment. In addition, detectable levels of the NKp30 ligand sB7-H6 predicted a worse prognosis in metastatic GIST. Soluble BAG6, an alternate ligand for NKp30 was associated with low NKp30 transcription and had additional predictive value in GIST patients with high NKp30 expression. Such GIST microenvironments could be rescued by therapy based on rIFN-α and anti-TRAIL mAb which reinstated innate immunity.